Biochar-loaded nano iron-copper material for treating hexavalent chromium wastewater as well as preparation method and application of biochar-loaded nano iron-copper material

By loading nano-iron-copper materials on biochar, the problem of insufficient nano-iron reactivity is solved, and the hexavalent chromium pollution in water is effectively removed. The material preparation is economical and environmentally friendly, and it is suitable for wastewater treatment.

CN119281296APending Publication Date: 2025-01-10CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411503431.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, nanoferrous iron has insufficient reactivity and precipitate accumulation is prone to form on the surface, making it difficult to efficiently remove hexavalent chromium (Cr(VI) pollution in water.

Method used

Biochar is used to load nano-iron-copper materials, and biochar is prepared by pyrolysis of white tea branches and leaves, and react with plant extract and iron-copper salt solution in a nitrogen environment to form nano-iron-copper composite materials for adsorption and reduction of water. Cr(VI).

Benefits of technology

The reactivity and removal ability of nano-ferrous iron are improved, and Cr(VI) in water is efficiently removed through electrostatic adsorption, coordination, redox and electron transfer, and the material is prepared from plant waste, with low economic costs and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281296A_ABST
    Figure CN119281296A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of remediation of heavy metal polluted underground water, and discloses a biochar-loaded nano iron-copper material for treating hexavalent chromium wastewater as well as a preparation method and application of the biochar-loaded nano iron-copper material. The preparation method of the material comprises the following steps: S1, mixing waste white tea branch and leaf powder with deionized water, heating in a water bath, and carrying out vacuum suction filtration to obtain a white tea extracting solution and white tea branch and leaf powder; s2, the white tea branch and leaf powder is placed in a drying oven to be dried, pyrolyzed, ground and sieved, and charcoal powder is obtained; s3, mixing the charcoal powder and the white tea extract in a liquid nitrogen gas environment to obtain a suspension; and dropwise adding an iron salt solution and a bivalent copper salt solution, and after the synthesis reaction is completed, centrifuging, washing and freeze-drying to obtain a finished product of the biochar-loaded nano iron-copper material. The biochar-loaded nano iron-copper material has higher reducing capacity for hexavalent chromium ions in water, is prepared from plant wastes and the like, does not involve the use of strong acids, strong bases and strong reducing agents, and has lower economic cost and higher environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of repairing heavy metal-contaminated groundwater, in particular to a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, a preparation method and application thereof. Background Art

[0002] Chromium (Cr) is often used in electroplating, manufacturing, dyeing and other industries due to its unique chemical properties, but due to irregular operations in the production process, it may be directly discharged into the soil and groundwater. Cr exists in water mainly in two oxidation states: hexavalent chromium (Cr(VI)) and trivalent chromium (Cr(III)), but Cr(VI) poses a huge threat to human health and ecosystems due to its high toxicity and high mobility. The remediation of Cr(VI) in water often adopts the adsorption reduction method, which is based on the principle of reducing highly toxic Cr(VI) to low-toxic Cr(III) through chemical reactions such as electron transfer, and finally removing it in the form of precipitation. Common reducing agents such as sulfites will cause secondary pollution to the environment. Therefore, it is very important to develop a new type of green material to remove Cr(VI) from water.

[0003] Nano-zero-valent iron (FeNPs) is highly favored in soil and groundwater heavy metal remediation due to its large specific surface area and high reactivity. Traditional methods for synthesizing FeNPs have disadvantages such as high synthesis cost and secondary pollution to the environment. Plant extracts are rich in macromolecular substances such as phenols and aldehydes, which can act as reducing agents and stabilizers, and can reduce Fe(II) / Fe(III) in the solution to Fe 0 Biochar (BC) is made by pyrolysis of waste crops, sludge, etc. under high temperature and anaerobic environment. Its rich functional groups, complex pore structure and large specific surface area are often used to adsorb heavy metal ions in water. If the extracted plant residues can be further processed to obtain BC to load green synthesized FeNPs, it will not only reduce the aggregation of FeNPs, but also increase the reaction area of ​​FeNPs and Cr(VI).

[0004] When FeNPs remove Cr(VI), the Fe(III) and Cr(III) generated will combine with -OH in water to form iron-chromium hydroxide precipitation attached to the surface of FeNPs, thereby reducing the reaction sites with Cr(VI). It has been reported that the introduction of transition metals such as nickel and manganese doped modified nano-iron can promote electron transfer on the FeNPs surface when reacting with Cr(VI). The principle is that Fe(III) obtains the electrons lost after oxidation by the transition metal and is reduced to Fe(II), thereby continuing the reaction with Cr(VI). Therefore, it is very necessary to find a moderately priced and stable metal-doped modified nano-iron to enhance the removal of Cr(VI) in water. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the problems in the prior art such as insufficient reaction activity of nano-iron and easy accumulation of precipitates on the surface during the reaction, and to provide a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, a preparation method and its application.

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] A method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, specifically comprising the following steps:

[0008] Step S1, mixing 40-60 g of waste white tea branch and leaf powder with 1 L of deionized water, heating in a water bath at 60-80° C. for 1 h, and vacuum filtering to obtain a liquid and a solid, wherein the liquid is a white tea extract and the solid is the white tea branch and leaf powder;

[0009] Step S2, placing the white tea branch and leaf powder obtained in step S1 in an oven to dry, and then placing it in a tubular furnace for pyrolysis, keeping nitrogen flowing during the pyrolysis process, grinding and sieving to obtain biochar powder;

[0010] Step S3, under a nitrogen environment, fully mix the biochar powder obtained in step S2 and the white tea extract obtained in step S1 under a nitrogen environment to obtain a suspension; add iron salt solution and divalent copper salt solution drop by drop into the suspension, and keep nitrogen flowing during the synthesis process; after the synthesis reaction is completed, centrifuge, wash and freeze-dry the synthesized product to obtain a finished biochar-loaded nano-iron-copper material.

[0011] Furthermore, in step S2, the pyrolysis conditions are: heating from room temperature to 500°C, maintaining for 1 hour, and then heating to 600°C and pyrolyzing for 4 hours, with a heating rate of 5°C·min -1 .

[0012] Furthermore, in step S3, the volume ratio of the white tea extract, the iron salt solution and the divalent copper salt solution is 6:(2-4):(1-2).

[0013] Furthermore, the dosage of biochar powder in step S3 is 0.83-2.50 g·L -1 .

[0014] Furthermore, the iron salt solution in step S3 is FeSO 4 7H 2 O solution, FeCl 3 6H 2 O solution, Fe(NO 3 ) 3 9H 2 O solution, the concentration of iron salt in the iron salt solution is 0.05~0.15mol·L -1 .

[0015] Furthermore, the divalent copper salt solution in step S3 is CuCl 2 ·2H 2 O solution, CuSO 4 ·5H 2 O solution, the concentration of divalent copper salt in the divalent copper salt solution is 0.025~0.075mol·L -1 .

[0016] A biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater is prepared by the above-mentioned preparation method.

[0017] An application of the above-mentioned biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater specifically comprises the following steps:

[0018] Step a, taking hexavalent chromium wastewater into a conical flask, adding dilute hydrochloric acid and sodium hydroxide solution to adjust the pH value of the hexavalent chromium wastewater, then adding biochar-loaded nano-iron-copper material, and continuously stirring at a rate of 150 rpm until the reaction is balanced;

[0019] Step b, sampling the supernatant at a fixed time point and filtering through a 0.22 μm syringe filter;

[0020] Step c, using diphenylcarbazide spectrophotometry at a wavelength of 540 nm to determine the hexavalent chromium concentration in the supernatant.

[0021] Furthermore, in step a, the pH value of the hexavalent chromium wastewater is 4 to 10, and the dosage of the biochar-loaded nano-iron-copper material is 0.45 to 1.05 g·L -1 ; The reaction temperature is 25-40℃; The initial concentration of hexavalent chromium in the hexavalent chromium wastewater is 20-50mg·L -1 .

[0022] The beneficial effects of the present invention are: the present invention has a reasonable design, a simple preparation method, and has the following advantages:

[0023] (1) The biochar-loaded nano-iron-copper material of the present invention has a stronger reducing ability for hexavalent chromium ions in wastewater, and can remove Cr(V) in water by electrostatic adsorption, coordination, oxidation-reduction, electron transfer, and coprecipitation;

[0024] (2) The biochar-loaded nano-iron-copper material of the present invention is prepared from plant waste and the like, and does not involve the use of strong acids, strong bases, and strong reducing agents, and has the advantages of wide sources, low economic costs, and high environmental benefits;

[0025] (3) The invention introduces copper-doped nano-zero-valent iron composite materials, which have lower economic costs compared to metals such as nickel and cobalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is the SEM-EDS image of TE-FeNPs / Cu-BC obtained in Example 1;

[0028] Figure 2 is the XRD pattern of TE-FeNPs / Cu-BC obtained in Example 1;

[0029] Figure 3 is the FTIR graph of TE-FeNPs / Cu-BC obtained in Example 1;

[0030] Figure 4 is the thermogravimetric analysis diagram of TE-FeNPs / Cu-BC obtained in Example 1;

[0031] Figure 5 is the nitrogen-adsorption-desorption curve of TE-FeNPs / Cu-BC obtained in Example 1;

[0032] Figure 6 It is the kinetics and isotherm curve fitting of the reaction between TE-FeNPs / Cu-BC and Cr(VI) obtained in Example 1; wherein, a. pseudo-first-order kinetic fitting, b. pseudo-second-order kinetic fitting, c. intra-particle diffusion model fitting, d. adsorption isotherm curve fitting. DETAILED DESCRIPTION

[0033] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] A method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, specifically comprising the following steps:

[0037] Step S1, mixing 40-60 g of waste white tea branch and leaf powder with 1 L of deionized water, heating in a water bath at 60-80° C. for 1 h, and vacuum filtering to obtain a liquid and a solid, wherein the liquid is a white tea extract and the solid is the white tea branch and leaf powder;

[0038] Step S2, placing the white tea branch and leaf powder obtained in step S1 in an oven to dry, and then placing it in a tubular furnace for pyrolysis, keeping nitrogen flowing during the pyrolysis process, grinding and sieving to obtain biochar powder;

[0039] Step S3, under a nitrogen environment, fully mix the biochar powder obtained in step S2 and the white tea extract obtained in step S1 under a nitrogen environment to obtain a suspension; add iron salt solution and divalent copper salt solution drop by drop into the suspension, and keep nitrogen flowing during the synthesis process; after the synthesis reaction is completed, centrifuge, wash and freeze-dry the synthesized product to obtain a finished biochar-loaded nano-iron-copper material.

[0040] In step S2, the pyrolysis conditions are to heat from room temperature to 500°C and hold for 1 hour, then continue to heat to 600°C and pyrolyze for 4 hours, with a heating rate of 5°C·min -1 .

[0041] In step S3, the volume ratio of the white tea extract, the iron salt solution and the divalent copper salt solution is 6:(2-4):(1-2).

[0042] The dosage of biochar powder in step S3 is 0.83-2.50 g·L -1 .

[0043] The iron salt solution in step S3 is FeSO 4 7H 2 O solution, FeCl 3 6H 2 O solution, Fe(NO 3 ) 3 9H 2 O solution, the concentration of iron salt in the iron salt solution is 0.05~0.15mol·L -1 .

[0044] The divalent copper salt solution in step S3 is CuCl2 ·2H 2 O solution, CuSO 4 ·5H 2 O solution, the concentration of divalent copper salt in the divalent copper salt solution is 0.025~0.075mol·L -1 .

[0045] A biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater is prepared according to the preparation method.

[0046] An application of biochar-loaded nano-iron-copper materials for treating hexavalent chromium wastewater specifically comprises the following steps:

[0047] Step a, taking hexavalent chromium wastewater into a conical flask, adding dilute hydrochloric acid and sodium hydroxide solution to adjust the pH value of the hexavalent chromium wastewater, then adding biochar-loaded nano-iron-copper material, and continuously stirring at a rate of 150 rpm until the reaction is balanced;

[0048] Step b, sampling the supernatant at a fixed time point and filtering through a 0.22 μm syringe filter;

[0049] Step c, using diphenylcarbazide spectrophotometry at a wavelength of 540 nm to determine the hexavalent chromium concentration in the supernatant.

[0050] In step a, the pH value of the hexavalent chromium wastewater is 4-10, and the dosage of the biochar-loaded nano-iron-copper material is 0.45-1.05 g·L -1 ; The reaction temperature is 25-40℃; The initial concentration of hexavalent chromium in the hexavalent chromium wastewater is 20-50mg·L -1 .

[0051] Example 1

[0052] A method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, specifically comprising the following steps:

[0053] Step S1, discarded white tea branches and leaves (taken from a tea factory in Liyang City, Changzhou, Jiangsu Province) were washed with deionized water and ethanol for 3 times each, then transferred to an oven at 60°C and dried to constant weight, ground into powder, and passed through a 100-mesh sieve to obtain discarded white tea branches and leaves powder; 60g of discarded white tea branches and leaves powder was mixed with 1L of deionized water, heated in a water bath at 80°C for 1h, and vacuum filtered through a 0.45μm filter membrane to obtain a liquid and a solid, wherein the liquid is a white tea extract and the solid is the white tea branches and leaves powder;

[0054] Step S2, collecting the white tea branch and leaf powder obtained in step S1 into a beaker, placing it in an oven at 80°C and drying it to constant weight; preparing biochar from the dried waste white tea branch and leaf powder by an anaerobic temperature-controlled slow pyrolysis method, the pyrolysis conditions are heating from room temperature to 500°C and maintaining for 1 hour, then continuing to heat to 600°C and pyrolyzing for 4 hours, and the heating rate is 5°C·min -1 During the pyrolysis process, nitrogen was kept flowing. After the pyrolysis was completed, the biochar was cooled to room temperature and then ground through a 200-mesh sieve to obtain biochar powder, which was recorded as BC.

[0055] Step S3: First, add 600 mL of the white tea extract obtained in step S1 into a three-necked flask, then add 1 g of BC obtained in step S2, and stir at 350 rpm for 30 min under a nitrogen environment to ensure that BC and the white tea extract are fully mixed to obtain a suspension; then add FeSO 4 7H 2 O solution (0.1 mol·L -1 ) and CuSO 4 ·5H 2 O solution (0.05 mol·L -1 ), V 茶 :V 铁 :V 铜 =6:2:1, and nitrogen was kept flowing during the synthesis process; after reacting for 2 hours, the solution was quickly transferred into a centrifuge tube and centrifuged at 8000 rpm. The solid at the bottom of the centrifuge tube was collected, washed with deionized water and anhydrous ethanol for 3 times each, and freeze-dried for 24 hours to obtain black nano-iron-copper particles, which were the finished biochar-loaded nano-iron-copper materials, recorded as TE-FeNPs / Cu-BC.

[0056] A biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater is prepared according to the preparation method.

[0057] An application of biochar-loaded nano-iron-copper materials for treating hexavalent chromium wastewater specifically comprises the following steps:

[0058] Step a: Take 50 mL of hexavalent chromium wastewater (the initial concentration of hexavalent chromium is 40 mg / L -1 ) in a conical flask, and the reaction temperature was adjusted to 30°C; dilute hydrochloric acid and sodium hydroxide solution were added to adjust the pH value of the hexavalent chromium wastewater to 4, and TE-FeNPs / Cu-BC was added, wherein the dosage of TE-FeNPs / Cu-BC was 0.85 g·L -1 ; Then continue stirring at 150 rpm until the reaction is balanced;

[0059] Step b, sampling the supernatant at a fixed time point and filtering through a 0.22 μm syringe filter;

[0060] Step c, using diphenylcarbazide spectrophotometry at a wavelength of 540 nm to determine the hexavalent chromium concentration in the supernatant.

[0061] The surface morphology and element distribution of TE-FeNPs / Cu-BC in this embodiment were analyzed by SEM-EDS. Figure 1 .Depend on Figure 1 It can be seen that TE-FeNPs / Cu-BC can be fixed on the BC surface uniformly and dispersedly like a ball chain, and the element contents are C (58.8%), O (29.95%), Fe (7.63%), and Cu (3.62%) respectively.

[0062] The structural composition of TE-FeNPs / Cu-BC in this embodiment was analyzed by X-ray powder diffractometer. Figure 2 .Depend on Figure 2 It can be seen that 20.56° and 25° are characteristic peaks of organic components in BC and white tea extract. 44.9° is α-Fe 0 The weak diffraction peak at 35° is Fe 2 O 3 The characteristic diffraction peak at 62.3° is attributed to Fe 3 O 4 , indicating that the material was slightly oxidized during the preparation process. 38.3° and 50° correspond to CuO and Cu 0 .

[0063] The functional group composition of TE-FeNPs / Cu-BC in this embodiment was analyzed by Fourier transform infrared spectroscopy. Figure 3 .Depend on Figure 3 It can be seen that 3416.67cm -1 The peak at 2852.61 cm is attributed to the stretching vibration of -OH in adsorbed water and OH in Fe / Cu oxide. -1 、1637.14cm -1 The peaks at 2921.91cm correspond to CH and C=C respectively. -1 Chuyou-CH 2 Caused by stretching vibration. 2361.72cm -1 CO 2 Anti-stretching vibration peak. 1094.39 / 1042.84cm -1 The corresponding absorption peak is CO.

[0064] 450-850cm -1 The range corresponds to the stretching vibrations of Fe-O and Cu-O.

[0065] The thermal stability of TE-FeNPs / Cu-BC in this example was analyzed by thermogravimetric analyzer. Figure 4 .Depend on Figure 4 It can be seen that the first weight loss interval of TE-FeNPs / Cu-BC is between 50 and 128.9°C, and the mass decreases by about 8.28%, which is caused by the evaporation of free water in the material during the heating process. The second weight loss interval is between 128.9 and 506.9°C, and the mass decreases by about 42.39%, which is attributed to the pyrolysis of organic components on its surface. The third weight loss interval is between 506.9 and 807.8°C, and the mass decreases by about 15.69%, which is caused by the pyrolysis of iron oxides and copper oxides. At the end of the test, the residual mass was about 32.96%, but the reaction equilibrium state was not reached at this time, indicating that some iron copper oxides and BC have not yet been completely pyrolyzed.

[0066] The specific surface area of ​​TE-FeNPs / Cu-BC in this embodiment was analyzed by thermogravimetric analyzer. Figure 5 .Depend on Figure 5 It can be seen that the N 2 The adsorption-desorption curves conform to the IV type isotherm, and the resulting hysteresis loop is of H3 type, indicating that the material is mainly mesoporous.

[0067] Example 2

[0068] The difference from Example 1 is that in this example, in step S1, the amount of waste white tea branch and leaf powder is 40 g, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0069] Example 3

[0070] The difference from Example 1 is that in this example, in step S1, the amount of waste white tea branch and leaf powder is 50 g, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0071] Examples 1 to 3 specifically used different masses of discarded white tea branch and leaf powder. The TE-FeNPs / Cu-BC prepared in Examples 1 to 3 were respectively applied to the removal of Cr(VI). The removal effects are compared as shown in Table 1.

[0072] Table 1 Test results of Cr(VI) removal in Examples 1 to 3

[0073] Cr(VI) removal rate Example 1 92.28% Example 2 60.17% Example 3 69.83%

[0074] As can be seen from Table 1, the TE-FeNPs / Cu-BC synthesized from different waste white tea branches and leaves powders have different activities in removing Cr(VI) from water. The reason is that the waste white tea branches and leaves powder contains insufficient reducing macromolecules, so that the synthesized TE-FeNPs / Cu-BC surface lacks sufficient reducing macromolecules. Therefore, the amount of waste white tea branches and leaves powder is preferably 60g.

[0075] Example 4

[0076] The difference from Example 1 is that in this example, in step S1, the water bath heating temperature is 60° C., and the remaining steps are the same as those in Example 1. The Cr(VI) concentration in the supernatant is measured by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0077] Example 5

[0078] The difference from Example 1 is that in this example, in step S1, the water bath heating temperature is 70° C., and the remaining steps are the same as Example 1. The Cr(VI) concentration in the supernatant is measured by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0079] Example 1, Example 4 and Example 5 specifically adopted different water bath heating temperatures. The TE-FeNPs / Cu-BC prepared in Example 1, Example 4 and Example 5 were respectively applied to the removal of Cr(VI). The removal effects are compared as shown in Table 2.

[0080] Table 2 Test results of Cr(VI) removal in Example 1, Example 4 and Example 5

[0081] Cr(VI) removal rate Example 1 92.28% Example 4 70.45% Example 5 71.22%

[0082] It can be seen from Table 2 that when the water bath heating temperature is at a higher level, the white tea extract obtained at this time can synthesize more active TE-FeNPs / Cu-BC, so the water bath heating temperature is preferably 80°C.

[0083] Example 6

[0084] The difference from Example 1 is that in this example, in step S3, 0.5 g of BC prepared in step S2 is added, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0085] Example 7

[0086] The difference from Example 1 is that in this example, in step S3, 1.5 g of BC prepared in step S2 is added, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0087] Example 1, Example 6 and Example 7 specifically used BC of different masses. The TE-FeNPs / Cu-BC prepared in Example 1, Example 6 and Example 7 were applied to the removal of Cr(VI). The removal effects were compared as shown in Table 3.

[0088] Table 3 Test results of Cr(VI) removal in Example 1, Example 6 and Example 7

[0089] Cr(VI) removal rate Example 1 92.28% Example 6 81.19% Example 7 85.13%

[0090] It can be concluded from Table 3 that the amount of biochar BC has a great influence on the chromium removal activity of the synthesized TE-FeNPs / Cu-BC. The reason is that the biochar itself not only provides a large specific surface area for the attachment of TE-FeNPs / Cu-BC, but also has a strong adsorption effect on Cr(VI) in water. In addition, excessive biochar will increase the distance between different iron cores, making the electrostatic attraction effect on Cr(VI) worse. Therefore, the amount of biochar BC is preferably 1g.

[0091] Example 8

[0092] The difference from Example 1 is that in this embodiment, in step S3, the iron salt solution is FeSO 4 6H 2 O solution, and the remaining steps are the same as in Example 1. The Cr(VI) concentration in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0093] Example 9

[0094] The difference from Example 1 is that in this embodiment, in step S3, the iron salt solution is FeSO 4 9H 2 O solution, and the remaining steps are the same as in Example 1. The Cr(VI) concentration in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0095] Example 1, Example 8 and Example 9 specifically used different iron salt solutions. The TE-FeNPs / Cu-BC prepared in Example 1, Example 8 and Example 9 were respectively applied to the removal of Cr(VI). The removal effects were compared as shown in Table 4.

[0096] Table 4 Test results of Cr(VI) removal in Example 1, Example 8 and Example 9

[0097] Cr(VI) removal rate Example 1 92.28% Example 8 83.12% Example 9 84.11%

[0098] As shown in Table 4, the TE-FeNPs / Cu-BC synthesized with different iron salts has a greater influence on the removal of Cr(VI) in water. It has a stronger affinity for Cr(VI) in water, so the iron salt solution is preferably FeSO 4 7H 2 O solution.

[0099] Example 10

[0100] The difference from Example 1 is that in this embodiment, in step S3, the divalent copper salt solution used is CuCl 2 ·2H 2 O solution, and the remaining steps are the same as in Example 1. The Cr(VI) concentration in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0101] Example 1 and Example 10 specifically used different divalent copper salt solutions. The TE-FeNPs / Cu-BC prepared in Example 1 and Example 10 were applied to the removal of Cr(VI). The removal effects were compared as shown in Table 5.

[0102] Table 5 Test results of Cr(VI) removal in Example 1 and Example 10

[0103] Cr(VI) removal rate Example 1 92.28% Example 10 83.12%

[0104] From Table 5, we can see that due to sulfate ions CuCl has a stronger affinity for Cr(VI) in water, so 2 ·2H 2 O-synthesized TE-FeNPs / Cu-BC has a poor removal effect on Cr(VI), so the divalent copper salt solution is preferably CuSO 4 ·5H 2 O.

[0105] Embodiment 11

[0106] The difference from Example 1 is that in this embodiment, in step S3, FeSO 4 7H 2 The concentration of O solution is 0.05 mol·L -1 , and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0107] Example 12

[0108] The difference from Example 1 is that in this embodiment, in step S3, FeSO 4 7H 2 The concentration of O solution is 0.15 mol·L -1 , and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0109] Example 1, Example 11 and Example 12 specifically used iron salt solutions of different concentrations. The TE-FeNPs / Cu-BC prepared in Example 1, Example 11 and Example 12 were respectively applied to the removal of Cr(VI), and the removal effects were compared as shown in Table 6.

[0110] Table 6 Test results of Cr(VI) removal in Example 1, Example 11 and Example 12

[0111] Cr(VI) removal rate Example 1 92.28% Embodiment 11 86.71% Example 12 72.11%

[0112] As shown in Table 6, when the concentration of the iron salt solution is too high or too low, the removal effect of the synthesized TE-FeNPs / Cu-BC on Cr(VI) in water is low. The reason is that when the amount of reducing macromolecules in the white tea extract is constant, when the concentration of the iron salt solution is high, the high-valent iron salt cannot be completely reduced. When the concentration of the iron salt solution is low, the iron core is completely wrapped by reducing macromolecules, making it difficult for Cr(VI) to approach Fe 0 nuclear.

[0113] Embodiment 13

[0114] The difference from Example 1 is that in this embodiment, in step S3, CuSO 4 ·5H 2 The concentration of O solution is 0.025 mol·L -1 , and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0115] Embodiment 14

[0116] The difference from Example 1 is that in this embodiment, in step S3, CuSO 4 ·5H 2 The concentration of O solution is 0.075 mol·L -1 , and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0117] Example 1, Example 13 and Example 14 specifically used divalent copper salt solutions of different concentrations. The TE-FeNPs / Cu-BC prepared in Example 1, Example 13 and Example 14 were respectively applied to the removal of Cr(VI), and the removal effects were compared as shown in Table 7.

[0118] Table 7 Test results of Cr(VI) removal in Example 1, Example 13 and Example 14

[0119] Cr(VI) removal rate Example 1 92.28% Embodiment 13 81.29% Embodiment 14 79.99%

[0120] It can be seen from Table 7 that the removal effect of Cr(VI) in water by synthesized TE-FeNPs / Cu-BC is different when the concentration of divalent copper salt solution is different. The role of copper doping is to promote the 3+ , Fe 2+ The electron transfer between Fe 3+ Reduced to Fe 2+ , and Cu 0 , Cu + It is converted to Cu by losing electrons 2+ When the concentration of the divalent copper salt solution is low, the galvanic cell system cannot be completely formed between iron and copper, which reduces the removal effect of Cr(VI). 0 , Fe 2+ As the ratio decreases, the removal effect will also deteriorate. Therefore, the concentration of the divalent copper salt solution is preferably 0.05 mol·L -1 .

[0121] Embodiment 15

[0122] The difference from Example 1 is that in this embodiment, in step S3, V 茶 :V 铁 :V 铜 =6:3:1, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0123] Example 16

[0124] The difference from Example 1 is that in this embodiment, in step S3, V 茶 :V 铁 :V 铜 =6:4:1, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0125] Embodiment 17

[0126] The difference from Example 1 is that in this embodiment, in step S3, V 茶 :V 铁 :V 铜 =6:3:2, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0127] In Example 1 and Example 15 to Example 17, the specific contents are as follows: different volume ratios of white tea extract, iron salt solution and copper salt solution. The TE-FeNPs / Cu-BC prepared in Example 1 and Example 15 to Example 17 are applied to the removal of Cr(VI), and the removal effects are compared as shown in Table 8.

[0128] Table 8 Test results of Cr(VI) removal in Example 1, Example 15 to Example 17

[0129]

[0130]

[0131] From Table 8, we can see that when V 茶 :V 铁 :V 铜 =6:2:1, the synthesized TE-FeNPs / Cu-BC has a stronger ability to remove Cr(VI). At this time, the reducing macromolecules in the white tea extract can make Fe 2+ , Cu 2+ is completely reduced, therefore, V is preferred 茶 :V 铁 :V 铜 =6:2:1.

[0132] Embodiment 18

[0133] The difference from Example 1 is that in this example, in step a, the pH value of the hexavalent chromium wastewater is adjusted to 6, and the remaining steps are the same as those in Example 1. The Cr(VI) concentration in the supernatant is measured at a wavelength of 540 nm using diphenylcarbazide spectrophotometry.

[0134] Embodiment 19

[0135] The difference from Example 1 is that in this example, in step a, the pH value of the hexavalent chromium wastewater is adjusted to 8, and the remaining steps are the same as those in Example 1. The Cr(VI) concentration in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0136] Embodiment 20

[0137] The difference from Example 1 is that in this example, in step a, the pH value of the hexavalent chromium wastewater is adjusted to 10, and the remaining steps are the same as those in Example 1. The Cr(VI) concentration in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0138] Example 1 and Example 18 to Example 20 specifically adjusted hexavalent chromium wastewater with different pH values. Example 1 and Example 18 to Example 20 were respectively applied to the removal of Cr(VI), and the removal effects were compared as shown in Table 9.

[0139] Table 9 Test results of Cr(VI) removal in Example 1, Example 18 to Example 20

[0140]

[0141]

[0142] It can be seen from Table 9 that when the solution is alkaline, OH - When the solution is acidic, the excess H + It will corrode the oxide layer on its surface, thereby accelerating electron transfer and increasing the removal rate of Cr(VI). The reaction between BC and Cr(VI) involves less electron exchange, while physical adsorption dominates. As a single material, TE-FeNPs has a smaller specific surface area, which limits the number of surface reaction sites. Therefore, TE-FeNPs / Cu-BC as a composite material has the ability to efficiently remove Cr(VI). Therefore, the pH value of hexavalent chromium wastewater is preferably adjusted to 4.

[0143] Embodiment 21

[0144] The difference from Example 1 is that in this example, in step a, the reaction temperature is adjusted to 25° C., and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0145] Embodiment 22

[0146] The difference from Example 1 is that in this example, in step a, the reaction temperature is adjusted to 35° C., and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0147] Embodiment 23

[0148] The difference from Example 1 is that in this example, in step a, the reaction temperature is adjusted to 40° C., and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant is determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0149] Example 1 and Example 21 to Example 23 specifically adjusted different reaction temperatures. Example 1 and Example 21 to Example 23 were respectively applied to the removal of Cr(VI), and the removal effects were compared as shown in Table 10.

[0150] Table 10 Test results of Cr(VI) removal in Example 1, Example 21 to Example 23

[0151] Cr(VI) removal rate Example 1 92.28% Embodiment 21 86.06% Embodiment 22 93.23% Embodiment 23 96.22%

[0152] It can be seen from Table 10 that when the reaction temperature increases, the Cr(VI) in the solution has a faster migration rate, thereby accelerating the binding with the reactive active sites on the surface of TE-FeNPs / Cu-BC. At the same time, it also accelerates the corrosion of iron oxides on the surface of TE-FeNPs / Cu-BC, thereby increasing the direct binding of Cr(VI) with Fe 0 The reaction area of ​​the core. The increase in reaction temperature further stimulates the reactivity of the organic components on the surface of TE-FeNPs / Cu-BC, which increases the degree of freedom and disorder of the solid-liquid interface and accelerates the electron collision rate with Cr(VI). Therefore, considering economic factors, the reaction temperature is preferably 30°C.

[0153] Embodiment 24

[0154] The difference from Example 1 is that in this example, in step a, the initial concentration of Cr(VI) in the hexavalent chromium wastewater is 20 mg·L -1 , and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0155] Embodiment 25

[0156] The difference from Example 1 is that in this example, in step a, the initial concentration of Cr(VI) in the hexavalent chromium wastewater is 30 mg·L -1 , and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0157] Embodiment 26

[0158] The difference from Example 1 is that in this example, in step a, the initial concentration of Cr(VI) in the hexavalent chromium wastewater is 50 mg·L -1, and the remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0159] Example 1 and Example 24 to Example 26 are specifically as follows: the initial concentrations of Cr(VI) in the hexavalent chromium wastewater are different, and Example 1 and Example 24 to Example 26 are respectively applied to the removal of Cr(VI), and the removal effects are compared as shown in Table 11.

[0160] Table 11 Test results of Cr(VI) removal in Example 1, Example 24 to Example 26

[0161] Cr(VI) removal rate Example 1 92.28% Embodiment 24 97.52% Embodiment 25 93.33% Embodiment 26 79.42%

[0162] It can be seen from Table 11 that the initial concentration of Cr(VI) is inversely proportional to the removal rate. This is because there are limited reaction sites for Cr(VI) to bind to TE-FeNPs / Cu-BC. Therefore, considering economic factors and the removal of high-concentration hexavalent chromium wastewater, the initial concentration of C(VI) in hexavalent chromium wastewater is preferably 40 mg·L -1 .

[0163] Embodiment 27

[0164] The difference from Example 1 is that in this example, in step a, the dosage of TE-FeNPs / Cu-BC is 0.45 g·L -1 The remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0165] Embodiment 28

[0166] The difference from Example 1 is that in this example, in step a, the dosage of TE-FeNPs / Cu-BC is 0.65 g·L -1 The remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0167] Embodiment 29

[0168] The difference from Example 1 is that in this example, in step a, the dosage of TE-FeNPs / Cu-BC is 1.05 g·L -1 The remaining steps are the same as those in Example 1. The concentration of Cr(VI) in the supernatant was determined by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0169] The specific details of Example 1 and Example 27 to Example 29 are as follows: the dosage of TE-FeNPs / Cu-BC is different. Example 1 and Example 27 to Example 29 are respectively applied to the removal of Cr(VI), and the removal effects are compared as shown in Table 12.

[0170] Table 12 Test results of Cr(VI) removal in Example 1, Example 27 to Example 29

[0171] Cr(VI) removal rate Example 1 92.28% Embodiment 27 70.34% Embodiment 28 89.99% Embodiment 29 95.73%

[0172] It can be seen from Table 12 that the dosage of TE-FeNPs / Cu-BC is proportional to the removal rate of Cr(VI). As the reaction proceeds, a smaller dosage will lead to a decrease in the number of effective adsorption sites, while a larger dosage will cause electrostatic repulsion between TE-FeNPs / Cu-BC, thus shortening the time to reach reaction equilibrium. Therefore, the optimal dosage of TE-FeNPs / Cu-BC is 0.85 g·L -1 .

[0173] Comparative Example 1

[0174] The difference from Example 1 is that in this comparative example, the biochar powder BC prepared in step S2 is used to directly remove Cr(VI) in water, and the remaining steps are the same as those in Example 1. The Cr(VI) concentration in the supernatant is measured by diphenylcarbazide spectrophotometry at a wavelength of 540 nm.

[0175] Comparative Example 2

[0176] The difference from Example 1 is that in this comparative example, step S3 is as follows: firstly, the white tea extract obtained in step S1 is added to the three-necked flask, and FeSO is added dropwise to the white tea extract. 4 7H 2 O solution (0.1 mol·L -1 ), V 茶 :V 铁 =2:1, and nitrogen was kept flowing during the synthesis process; after reacting for 2 hours, the solution was quickly transferred into a centrifuge tube, centrifuged at 8000 rpm, the solid at the bottom of the centrifuge tube was collected, washed with deionized water and anhydrous ethanol for 3 times each, and freeze-dried for 24 hours to synthesize TE-FeNPs.

[0177] The TE-FeNPs / Cu-BC prepared in Example 1, the BC prepared in Comparative Example 1, and the TE-FeNPs prepared in Comparative Example 2 were applied to the removal of Cr(VI), and the removal effects were compared as shown in Table 13.

[0178] Table 13 Test results of Cr(VI) removal in Example 1, Comparative Example 1 and Comparative Example 2

[0179] Cr(VI) removal rate Example 1 92.28% Comparative Example 1 23.44% Comparative Example 2 67.71%

[0180] It can be seen from Table 13 that when the solution is alkaline, OH - When the solution is acidic, the excess H + It will corrode the oxide layer on its surface, thereby accelerating electron transfer and increasing the removal rate of Cr(VI). The reaction between BC and Cr(VI) involves less electron exchange, while physical adsorption dominates. As a single material, TE-FeNPs has a small specific surface area, which limits the number of surface reaction sites. Therefore, TE-FeNPs / Cu-BC as a composite material has the ability to efficiently remove Cr(VI).

[0181] In addition, the linear fitting of the reaction kinetics of TE-FeNPs / Cu-BC and Cr(VI) is shown in Figure 2. Figure 6 a, 6b, 6c, and the calculated reaction kinetic rate constants are shown in Table 14.

[0182] Table 14 Kinetic rate constants of the reaction between TE-FeNPs / Cu-BC and Cr(VI)

[0183]

[0184] Depend on Figure 6 a. Figure 6 b. As shown in Table 14, the Qe fitted by the two models increases with the increase of the initial concentration of Cr(VI), and the fitting coefficient of the pseudo-second-order kinetic model (R 2 =0.98~0.99) is higher than the fitting coefficient of the pseudo-first-order kinetic model (0.91~0.98), and the Qe fitted by the pseudo-second-order kinetic model is closer to Qeexp, K 2 The value of gradually decreases as the reaction proceeds, which indicates that chemical adsorption dominates the reaction process, there is electron transfer in the adsorption process, and the pseudo-second-order kinetic model is more suitable for describing the reaction process of TE-FeNPs / Cu-BC and Cr(VI). Figure 6 c shows that the reaction is divided into two stages: rapid adsorption and gradual slowing down. When the initial concentration of Cr(VI) increases, K d1 The curve after fitting does not pass through the origin, indicating that the reaction process of TE-FeNPs / Cu-BC and Cr(VI) will be affected by other factors such as liquid film diffusion and surface adsorption. Langmuir and Freundlich equation isotherm curve fitting can be seen in Figure 6d, the adsorption isotherm fitting parameters are shown in Table 14. Comparison of the R 2 , the reaction process between TE-FeNPs / Cu-BC and Cr(VI) is more consistent with the Langmuir equation model, which indicates that the adsorption sites on the surface of TE-FeNPs / Cu-BC are independent and evenly distributed and mainly monolayer adsorption. .RL is less than 1, indicating that the reaction process is favorable for adsorption. 1 / n is 0.21±0.03, which further confirms that TE-FeNPs / Cu-BC enhances the adsorption strength of Cr(VI).

[0185] In summary, the present invention has a reasonable design, a simple preparation method and the following advantages:

[0186] (1) The biochar-loaded nano-iron-copper material of the present invention has a stronger reducing ability for hexavalent chromium ions in wastewater, and can remove Cr(VI) from water by electrostatic adsorption, coordination, oxidation-reduction, electron transfer, and coprecipitation;

[0187] (2) The biochar-loaded nano-iron-copper material of the present invention is prepared from plant waste and the like, and does not involve the use of strong acids, strong bases, and strong reducing agents, and has the advantages of wide sources, low economic costs, and high environmental benefits;

[0188] (3) The invention introduces copper-doped nano-zero-valent iron composite materials, which have lower economic costs compared to metals such as nickel and cobalt.

[0189] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, characterized in that: The specific steps include: Step S1, mixing 40-60 g of waste white tea branch and leaf powder with 1 L of deionized water, heating in a water bath at 60-80° C. for 1 h, and vacuum filtering to obtain a liquid and a solid, wherein the liquid is a white tea extract and the solid is the white tea branch and leaf powder; Step S2, placing the white tea branch and leaf powder obtained in step S1 in an oven to dry, and then placing it in a tubular furnace for pyrolysis, keeping nitrogen flowing during the pyrolysis process, grinding and sieving to obtain biochar powder; Step S3, under a nitrogen environment, fully mix the biochar powder obtained in step S2 and the white tea extract obtained in step S1 under a nitrogen environment to obtain a suspension; add iron salt solution and divalent copper salt solution drop by drop into the suspension, and keep nitrogen flowing during the synthesis process; after the synthesis reaction is completed, centrifuge, wash and freeze-dry the synthesized product to obtain a finished biochar-loaded nano-iron-copper material.

2. The method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater according to claim 1, characterized in that: In step S2, the pyrolysis conditions are to heat from room temperature to 500°C and hold for 1 hour, then continue to heat to 600°C and pyrolyze for 4 hours, with a heating rate of 5°C·min -1 .

3. The method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater according to claim 1, characterized in that: In step S3, the volume ratio of the white tea extract, the iron salt solution and the divalent copper salt solution is 6:(2-4):(1-2).

4. The method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater according to claim 1, characterized in that: The dosage of biochar powder in step S3 is 0.83-2.50 g·L -1 .

5. The method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater according to claim 1, characterized in that: The iron salt solution in step S3 is one of FeSO4·7H2O solution, FeCl3·6H2O solution, and Fe(NO3)3·9H2O solution, and the concentration of the iron salt in the iron salt solution is 0.05-0.15 mol·L -1 .

6. The method for preparing a biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater according to claim 1, characterized in that: The divalent copper salt solution in step S3 is one of CuCl2·2H2O solution and CuSO4·5H2O solution, and the concentration of the divalent copper salt in the divalent copper salt solution is 0.025-0.075 mol·L -1 .

7. A biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater, characterized in that: The biochar-loaded nano-iron-copper material for treating hexavalent chromium wastewater is prepared according to the preparation method according to any one of claims 1 to 6.

8. An application of biochar-loaded nano-iron-copper materials for treating hexavalent chromium wastewater as claimed in claim 7, characterized in that: The application of the biochar-loaded nano-iron-copper material in treating hexavalent chromium wastewater specifically comprises the following steps: Step a, taking hexavalent chromium wastewater into a conical flask, adding dilute hydrochloric acid and sodium hydroxide solution to adjust the pH value of the hexavalent chromium wastewater, then adding biochar-loaded nano-iron-copper material, and continuously stirring at a rate of 150 rpm until the reaction is balanced; Step b, sampling the supernatant at a fixed time point and filtering through a 0.22 μm syringe filter; Step c: using diphenylcarbazide spectrophotometry at a wavelength of 540 nm to determine the hexavalent chromium concentration in the supernatant.

9. The use of biochar-loaded nano-iron-copper materials for treating hexavalent chromium wastewater according to claim 8, characterized in that: In step a, the pH value of the hexavalent chromium wastewater is 4-10, and the dosage of the biochar-loaded nano-iron-copper material is 0.45-1.05 g·L -1 ; The reaction temperature is 25-40℃; The initial concentration of hexavalent chromium in the hexavalent chromium wastewater is 20-50mg·L -1 .

Citation Information

Cited By

  • Heavy metal adsorption filler as well as preparation method and application thereof

    CN121372374A